Association between psoriasis and coronary artery calcification: A systematic review and meta-analysis - Wu, Huihui; Luo, Zeyu; Liu, Juanhua; Luo, Diqing; Song, Luli; Zhao, Yukun (Frontiers in Cardiovascular Medicine, 2022)
Background: Psoriasis and atherosclerosis have overlapping pathophysiological mechanisms. However, the association between psoriasis and coronary artery calcification (CAC), a hallmark of atherosclerosis and a predictor of poor cardiovascular prognosis, remains to be determined. We performed a systematic review and meta-analysis to comprehensively evaluate the association between these related inflammatory conditions. Methods: Observational studies evaluating the relationship between psoriasis and CAC were retrieved by searching PubMed, Cochrane’s Library, and Embase databases. Presence of CAC was confirmed according to an Agatston's Score >0 upon computed tomography examination. A random-effect model incorporating between-study heterogeneity was used to pool the results. Results: Sixteen studies involving 3,039 patients with psoriasis and 46,191 controls without psoriasis were included in the meta-analysis. All participants were without previously known cardiovascular diseases. Pooled results showed that psoriasis was associated with overall CAC (odds ratio [OR]: 1.54, 95% confidence interval: 1.23 to 1.91, p<0.001; I2 = 57%), after matching or adjusting the conventional cardiovascular risk factors. Subgroup analyses showed that study country, comorbidity of psoriatic arthritis, baseline Psoriasis Area and Severity Index, and duration of psoriasis (p for subgroup difference all >0.05) did not significantly affect the association of psoriasis and CAC. However, a stronger association was observed in younger patients (mean age <50 years, OR: 2.63, p<0.001) compared to older patients (≥50 years, OR: 1.24, p=0.02; p for subgroup difference <0.001). Conclusion: Psoriasis is associated with CAC, and the association may be stronger in younger patients.